Multi-dryer / Muhammad Nabil Rodzi ... [et al.] - Rodzi, Muhammad Nabil; Md Nasir, Nurul Farah Asyikin; Sarudin, Nurul Ashida; Ahmad, Mariah Fadhilah; Najibbollah, Nurulhana; Mohamad Yusoff, Nur Afiqah; Md Taib, Norraeffa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Introducing multi-dryer. It is known as a shoe dryer. The purpose of this multi dryer is to help people to dry their shoes in a fastest way and an easiest way, which keeping your shoes in a good hygiene shape. (Especially whenever there's a problem in letting your shoe dry because of bad weather forecast). Multi dryer follows through the heat, which the heat comes from the bulb which it uses air from the fan. There is an on and off button switch provide to handle. This Multi-dryer gives positive advantages to us which we can easily bring this multi-dryer to any places that we want (especially on a road trip). It is an affordable product and everyone is able to buy it. This product is suitable for all users. Easy to use product. The impact socio economic of multi-dryer is we can reduce the unemployment rate by letting them do business with this product. Chances of those who are un employed. This will increase our economy standard. This product is suitable to be commercialize because, nowadays people need are trying to find an instant product. If we introduce Multi-dryer, we could have the potential to attract people not only from our country but from other country as well.